The Effect of Implementing an Auction Item System and Social Factors on Profit and Loss Reports at PT. Pegadaian UPC Sukaria - Nurfelissha Az Zahra; Alamsjah Alamsjah; Firman Syah (Journal Social Society, 2026)
This study highlights the importance of auction systems and social factors in improving financial performance, operational efficiency, profitability, business sustainability, and contributing to empirical research on corporate auction mechanisms. The research adopts a quantitative descriptive–verificative approach conducted at PT Pegadaian (Persero) Sukaria UPC, Makassar. The study population consists of auction and financial records, with purposive sampling applied to select relevant data for analysis. Data collection is carried out using financial documents and structured questionnaires designed to measure social factors such as trust, perceived fairness, and awareness of the auction process. The questionnaires apply a Likert scale to ensure consistency in capturing respondents’ perceptions. Data analysis utilizes descriptive and inferential statistical methods, supported by classical assumption tests to ensure the validity and reliability of the regression model. The analytical procedures include descriptive statistics, simple linear regression analysis, normality testing, heteroscedasticity testing, and multicollinearity testing. A simple linear regression model is specifically employed to examine the effect of auction item implementation on profit and loss. The findings indicate that auction items have a positive and highly significant effect on profit and loss. The regression coefficient of 1.375, supported by a t-value of 9.235 and a p-value below 0.001, demonstrates a strong relationship between the value of auctioned items and financial performance. The F-test confirms the overall model’s statistical significance, with an F-value of 85.292 and a p-value below 0.001. The coefficient of determination (R²) of 0.914 indicates that 91.4% of the variation in profit and loss is explained by auction item value. These results highlight the effectiveness of auction mechanisms in increasing profitability and provide practical and theoretical insights into the relationship between auction systems, social dynamics, and financial performance.